“Another End of the World is Possible”. Revolt and Anarchivism - Tello, Andrés Maximiliano (Re-presentaciones: Periodismo, comunicación y sociedad, 2020)
This text proposes some lines of problematization on the link between anarchivism and revolt, in light of the events unleashed in Chile during the last months. To do this, we start by assuming an unconventional notion of the archive (Foucault, Derrida), understood here as a social machine (Deleuze and Guattari) that is responsible for establishing the hierarchical organization of the records of bodies in society. With special emphasis on the media and information archives, we delve into the ways in which the social archive machine has been complementary to the social order established by the neoliberal government during the last decades. Then, we analyze how the emergence of the revolt unleashes at the same time the proliferation of anarchivist machines, that is, bodies and technologies that destabilize the archive that supports the neoliberal order.
Keywords: Revolt; Anarchivism; Neoliberal order